Pembuatan Biodiesel Berbahan Baku CPO Menggunakan Reaktor Sentrifugal dengan Variasi Rasio Umpan dan Komposisi Katalis - Ardago Lengga Muda Siregar; Idral Idral; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of many sources of alternative fuel is biodiesel . Biodiesel production cost is still quite expensive, it need a technology to reduce thecost of biodiesel production . Centrifugal reactor technology is one of the alternative technology of biodiesel production, which is very likely to be developed .Study of biodiesel production using palm oil as the feedstock, methanol as the reagent, and NaOH as catalyst.This research use centrifugal reactor as the reactor, which has a pre-heater for feed, feed tank and pumps. The study was conducted at the reaction temperature of 60ºC with a residence time in the reactor for 2 hours . CPO mixture , methanol , and a catalyst in the feed the reactor with variation in the molar methanol : CPO ( 3:1 , 6:1 , 9:1 , 12:1 ) and the variation of the composition of the catalyst ( 0.5, 0.75, 1 % - w ) . From the results of the study showed that the molar ratio and catalyst composition affects the speed of the reaction to reach equilibrium reaction . The results showed biodiesel using centrifugal reactor reaches a yield of 92.6 % under the conditions of 9:1 molar ratio with 0.75 %-w catalyst . Characteristics of biodiesel produced in the form of viscosity , density , acid number , and flash point of biodiesel are qualified as Indonesian standards of Biodiesel.